Being Misunderstood as a Person: The Role of Identity, Reappraisal, and Perspective-Taking. Issue 5 (19th October 2020) - Edwards, Renee
ABSTRACT: Being misunderstood as a person occurs when an interaction partner communicates in a way that reveals a different view of one's identity than that held by the individual. Results of a study ( n = 282) revealed that both personal and social identities are misunderstood, with personality being misunderstood most frequently. Misunderstandings about religious beliefs are especially serious and negative. Reappraisal has a small effect on communication satisfaction while partner's perspective-taking has a more robust effect on communication satisfaction and emotion than the self's perspective-taking. As hypothesized, relational satisfaction was predicted by perspective-taking (especially the partner's), communication satisfaction, and the seriousness of the misunderstanding. A model of being misunderstood as a person is proposed.